2016
DOI: 10.1016/j.polymer.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of thin polymer film rupture: Model experiments for a better understanding of layer breakups in the multilayer coextrusion process

Abstract: We show that the kinetics of bursting of a thin film embedded in another polymer matrix can be well described by a simple equation balancing the viscous and capillary forces. The role of viscosity, interfacial tension and thickness of the layers under static conditions was investigated by adapting a simple model experiment initially designed to study the dewetting of a thin polymer film on another polymer substrate. Kinetics was correlated to instabilities occurring during multilayer coextrusion leading to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…To further test these hypotheses, simplified experiments on model systems containing a small number of layers can be envisioned. In a recent article, 81 we studied dewetting in a three-layer system (a thin PS film in between two thicker PMMA slabs) heated above both glass-transition temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…To further test these hypotheses, simplified experiments on model systems containing a small number of layers can be envisioned. In a recent article, 81 we studied dewetting in a three-layer system (a thin PS film in between two thicker PMMA slabs) heated above both glass-transition temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases it has been observed that this process is subject to instabilities which give rises to rupture of the layers [24,25], especially with complex polymers like MXD6. However, if the structures created are still under the form of elongated lamellas, they may still be of interest for gas barrier applications [26].…”
Section: Markmentioning
confidence: 99%
“…However, extrusion‐blown molding is not suitable for the preparation of brittle PS or particle‐embedded polymer membranes. Microlayer or nanolayer coextrusion is an advanced polymer processing technique that is capable of economically and efficiently producing films in multilayers with individual layer thicknesses varying from the micro‐ to nanoscale . Microlayer or nanolayer coextrusion has many advantages, including continuous processing, economic pathways for large‐scale fabrication, flexibility of the polymer species, and a tunable layer structure …”
Section: Introductionmentioning
confidence: 99%